Pengaruh Motivasi Terhadap Kinerja Pejabat Fungsional pada Dinas Pemadam Kebakaran Kabupaten Paser - Rusmiati Rusmiati; Achmad Aprianor Firdaus; Veronica Refiawati Pandiangan (Pusat Riset dan Inovasi Nasional, 2025)
This research was conducted to examine the effect of human needs based on Maslow’s hierarchy, consisting of Physiological Needs (X1), Security Needs (X2), Social Needs (X3), Esteem Needs (X4), and Self-Actualization Needs (X5), on the performance of Functional Officials (Y) at the Paser Regency Fire Department. The study applied a saturated sampling technique, where all 38 Functional Officials were included as respondents. Data analysis through multiple linear regression generated the equation Y = 1.219 + 0.567X1 + 0.001X2 + 0.706X3 – 0.178X4 – 0.126X5. The correlation coefficient (R) was 0.856, reflecting a very strong relationship between the independent variables and performance. Furthermore, the adjusted coefficient of determination (Adjusted R²) was 0.691, showing that 69.1% of performance variation could be explained by the five independent variables, while 30.9% was determined by other unobserved factors. The results of simultaneous testing indicated that the calculated F-value (17.520) was greater than the table value (2.51) with a significance level of 0.000 < 0.05, leading to the conclusion that all variables together significantly affect performance. Partial testing further revealed that Physiological Needs (X1), Social Needs (X3), and Esteem Needs (X4) had a significant positive influence, while Security Needs (X2) and Self-Actualization Needs (X5) showed no significant impact. Among these, Social Needs (X3) demonstrated the most dominant role based on the highest t-value. These findings emphasize that fulfilling social, physiological, and esteem-related needs is crucial to enhancing the performance of Functional Officials, highlighting the importance of interpersonal relations, recognition, and basic support in improving work outcomes at the Paser Regency Fire Department.